A Marxist Feminist Study in Walter Tevis' The Queen's Gambit - Asst. Lect. Zainab Abdulhasan AL-Almusawi; Dr. Doaa Taher Matrood AL-dihaymawee (Global Scientific Publishing, 2024)
The present research sheds light on Walter Tevis' The Queen's Gambit (1983) from a Marxist feminist perspective. This theory explores how gender ideologies of femininity and masculinity structure production in capitalism. By making the use value of reproductive labor visible, this theory contests the dominance of capitalist value in determining social values, including the exchange value in wages and the surplus value of profit. This study examines the movement's forerunners and Marxist feminist thoughts in the context of The Queen’s Gambit by Walter Tevis. The Queen’s Gambit is a story of an orphan girl, Beth, who is a genius at a chess game. In the 1950s, chess was allowed for men only, not women. However, Beth tries to prove herself in such a masculine world through a chess game, which she does through her success at the novel's end
Keywords: Feminism; Marxism; Marxist feminism